DLL4/Notch1 and BMP9 Interdependent Signaling Induces Human Endothelial Cell Quiescence via P27KIP1 and Thrombospondin-1. Issue 12 (December 2015) - Rostama, Bahman; Turner, Jacqueline E.; Seavey, Guy T.; Norton, Christine R.; Gridley, Thomas; Vary, Calvin P.H.; Liaw, Lucy
Abstract : Objective—: Bone morphogenetic protein-9 (BMP9)/activin-like kinase-1 and delta-like 4 (DLL4)/Notch promote endothelial quiescence, and we aim to understand mechanistic interactions between the 2 pathways. We identify new targets that contribute to endothelial quiescence and test whether loss of Dll4 +/ − in adult vasculature alters BMP signaling. Approach and Results—: Human endothelial cells respond synergistically to BMP9 and DLL4 stimulation, showing complete quiescence and induction of HEY1 and HEY2 . Canonical BMP9 signaling via activin-like kinase-1-Smad1/5/9 was disrupted by inhibition of Notch signaling, even in the absence of exogenous DLL4. Similarly, DLL4 activity was suppressed when the basal activin-like kinase-1-Smad1/5/9 pathway was inhibited, showing that these pathways are interdependent. BMP9/DLL4 required induction of P27 KIP1 for quiescence, although multiple factors are involved. To understand these mechanisms, we used proteomics data to identify upregulation of thrombospondin-1, which contributes to the quiescence phenotype. To test whether Dll4 regulates BMP/Smad pathways and endothelial cell phenotype in vivo, we characterized the vasculature of Dll4 +/ − mice, analyzing endothelial cells in the lung, heart, and aorta. Together with changes in endothelial structure and vascular morphogenesis, we found that loss of Dll4 was associated with a significant upregulation of pSmad1/5/9 signaling in lung endothelial cells. Because steady-state endothelial cell proliferation rates were not different in the Dll4 +/ − mice, we propose that the upregulation of pSmad1/5/9 signaling compensates to maintain endothelial cell quiescence in these mice. Conclusions—: DLL4/Notch and BMP9/activin-like kinase-1 signaling rely on each other's pathways for full activity. This represents an important mechanism of cross talk that enhances endothelial quiescence and sensitively coordinates cellular responsiveness to soluble and cell-tethered ligands. Abstract : Supplemental Digital Content is available in the text.